Ab initio metadynamics calculations of dimethylamine for probing pKb variations in bulk vs. surface environments. Issue 45 (11th November 2020) - Biswas, Sohag; Kwon, Hyuna; Barsanti, Kelley C.; Myllys, Nanna; Smith, James N.; Wong, Bryan M.
Abstract : Free energy landscape obtained from ab initio metadynamics calculations for dimethylamine protonation at the air–water interface. Abstract : The basicity constant, or p K b, is an intrinsic physical property of bases that gives a measure of its proton affinity in macroscopic environments. While the p K b is typically defined in reference to the bulk aqueous phase, several studies have suggested that this value can differ significantly at the air–water interface (which can have significant ramifications for particle surface chemistry and aerosol growth modeling). To provide mechanistic insight into surface proton affinity, we carried out ab initio metadynamics calculations to (1) explore the free-energy profile of dimethylamine and (2) provide reasonable estimates of the p K b value in different solvent environments. We find that the free-energy profiles obtained with our metadynamics calculations show a dramatic variation, with interfacial aqueous dimethylamine p K b values being significantly lower than in the bulk aqueous environment. Furthermore, our metadynamics calculations indicate that these variations are due to reduced hydrogen bonding at the air–water surface. Taken together, our quantum mechanical metadynamics calculations show that the reactivity of dimethylamine is surprisingly complex, leading to p K b variations that critically depend on the different atomic interactions occurring at the microscopic molecular level.